A Mini Review on Carbon Molecular Sieve Membrane for Oxygen Separation - Fatin Nurwahdah, Ahmad; Norazlianie, Sazali; Mohd Hafiz Dzafran, Othman (Penerbit UMP, 2020)
Membrane-based technology has proved its practicality in gas separation through its performance. Various type of membranes has been explored, showing that each type of them have their own advantages and disadvantages. Polymeric membranes have been widely used to separate O2/N2, however, its drawbacks lead to the development of carbon molecular sieve membrane. Carbon molecular sieve membranes have demonstrated excellent separation performance for almost similar kinetic diameter molecules such as O2/N2. Many polymer precursors can be used to produce carbon molecular sieve membrane through carbonization process or also known as heat treatment. This paper discusses the variety of precursors and carbonization parameters to produce high quality and performance of carbon molecular sieve membranes. This paper covers the evaluation in advancement and status of high-performance carbon membrane implemented for separating gas, comprising the variety of precursor materials and the fabrication process that involve many different parameters, also analysis of carbon membranes properties in separating various type of gas having high demand in the industries. The issues regarding the current challenges in developing carbon membrane and approaches with the purpose of solving and improving the performance and applications of carbon membrane are included in this paper. Also, the advantages of the carbon membrane compared to other types of membranes are highlighted. Observation and understanding the variables affecting the quality of membrane encourage the optimization of conditions and techniques in producing high-performance membrane.